Pengembangan Bahan Ajar Pengajaran Mikro Matematika Kelas SBI - Sujadi, Imam; Sugaiarto, Bambang (Kreano, Jurnal Matematika Kreatif-Inovatif, 2010)
This research aims at producing printed teaching materials for micro teaching program which can be used as one of learning resources for students of international standard school in Math Department. The main activity in this research is developing teaching material which is designed to support the achievement of teaching curricular i.e the students are capable of teaching math in international program. This covers two stages- exploration and developing draft model. In the first stage, the researchers performed related literatures reviews and collected varied information related to the problems faced by the students/ teachers in conducting teaching activities in international program. Based on the data gathered, the draft model was developed. Results of the research show that the English competence of the students in math department needs to be enhanced. Courses related to micro teaching program for international school should be rigorously planned, syllabus and its implementation in teaching learning process needs to be revised. In the micro teaching program for international standard school, students have to practice activities dealing with planning classroom management, using media, and developing lesson plan in English. The provision of teaching and learning resources for micro teaching program of international standard school in math department is far from sufficient level and needs improvement. Teaching materials developed cover how to start the lessons, structure the lesson, use learning aids/media, use textbooks, respond to students’ performance, and administer the exams. Developing varieties of teaching materials and their periodical revision are badly needed. Key words : English competence, micro teaching, teaching materials.